2016
DOI: 10.1371/journal.pone.0165616
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Non-Hydrostatic Numerical Dust Model by Integrating Soil Moisture and Greenness Vegetation Fraction Data with Different Spatiotemporal Resolutions

Abstract: Dust storms are devastating natural disasters that cost billions of dollars and many human lives every year. Using the Non-Hydrostatic Mesoscale Dust Model (NMM-dust), this research studies how different spatiotemporal resolutions of two input parameters (soil moisture and greenness vegetation fraction) impact the sensitivity and accuracy of a dust model. Experiments are conducted by simulating dust concentration during July 1–7, 2014, for the target area covering part of Arizona and California (31, 37, -118, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Moreover, a recent study describing a conceptual model of dust dynamics showed that vertical transport can efficiently counteracts and limits the gravitational settling of coarse particles [103], according to Lidar observations in the frame of the SALTRACE experiment. The evolution of the particle sizes is also shown in Figure 7 [35][36][37][38][39][40] • N resulting mainly of the trans-Pacific transport of Asian dust emissions mixed with diluted Saharan dust transported by southwesterly fluxes. In Figure 7, the deep convection updraft flux integrated over the column is displayed as an indicator of the convective activity.…”
Section: Particle Size Distributionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, a recent study describing a conceptual model of dust dynamics showed that vertical transport can efficiently counteracts and limits the gravitational settling of coarse particles [103], according to Lidar observations in the frame of the SALTRACE experiment. The evolution of the particle sizes is also shown in Figure 7 [35][36][37][38][39][40] • N resulting mainly of the trans-Pacific transport of Asian dust emissions mixed with diluted Saharan dust transported by southwesterly fluxes. In Figure 7, the deep convection updraft flux integrated over the column is displayed as an indicator of the convective activity.…”
Section: Particle Size Distributionmentioning
confidence: 90%
“…Differences due to a finer resolution are also associated to the channelization of the dust flow through valleys and the differences in the modeled altitude of the mountains that alters the meteorology and blocks the simulated dust fronts limiting the dust transport. For the USA, the use of the Non Hydrostatic Mesoscale Dust model at fine resolution [36] shows a large improvement of dust storm simulation thanks to the improvement of the quality of input data such as soil moisture and vegetation cover. A major West African dust storm was simulated at 5 km resolution with the French modeling system AROME coupled with the ORILAM aerosol model [37].…”
Section: Introductionmentioning
confidence: 99%
“…Differences due to a finer resolution are also associated to the channelization of the dust flow through valleys and the differences in the modelled altitude of the mountains that alters the meteorology and blocks the simulated dust fronts limiting the dust transport. For the USA, the use of the Non Hydrostatic Mesoscale Dust model at fine resolution [34] shows a large improvement of dust storm simulation thanks to the improvement of the quality of input data like soil moisture and vegetation cover. A major West African dust storm was simulated at 5km resolution with the French modelling system AROME coupled with the ORILAM aerosol model [35].…”
Section: Of 45mentioning
confidence: 99%
“…Here, we aim to evaluate the sensitivity of dust transport simulated by WRF-Chem to the Chappell and Webb (2016) albedo-based drag partition. Our analysis focused on a convective dust event case study from 3-4 July 2014 for the southwestern US desert region previously discussed in other published works (e.g., Hyde et al, 2018;Yu and Yang, 2016). The results from Hyde et al (2018), in particular, motivated our case study choice.…”
Section: Introductionmentioning
confidence: 99%